Produção diferencial de estimulos discriminativos por humanos: uma replicação de Mulvaney, Hughes, Jwaideh e Dinsmoor, 1981 - Pessôa, Candido Vinicius Bocaiuva Barnsley (2005)
The purpose of this research was to analyze the production of observing responses (OR) emitted by humans when the consequences were the production of stimuli related to a VI or EXT schedule. Six participants between 22 and 42 years old were distributed in 2 groups. Participants in Group 1 were first exposed to a multiple schedule VI 20s-EXT with components of 90 seconds in average. During the VI component, presses on a button produced points exchanged for money at the end of each session. After achieving 0.9 or more in a discrimination index (responses during VI divided by responses during VI plus responses during EXT) for 3 or more consecutive sessions, these participants were exposed to a mixed schedule VI 20s-EXT, with the possibility of emiting responses (OR) on a second button that changed the schedule from mixed to its multiple equivalent for the time the button remained pressed. Group 2 participants were exposed directly to this second condition. Participants of Group 2 achived discrimination indexes higher than 0,9 and Group 1 participants did not achived the criterion. The absence of dircrimination of the responses of Group 1 participants was discussed in terms of relevance of the stimuli produced by the OR and in terms of accidental chaining. All participants exposed to the mix VI EXT with OR produced OR. Two participants emitted OR in a situation where they represented effort economy. All participants produced the stimulus related to EXT in geater or equal frequency and duration than the stimulus related to VI